Review on the parasitic infections in Malayan sun bears (Helarctos malayanus) / Elden Zoumin .. [et al.] - Zoumin, Elden; Abdul Mawah, Siti Sarayati; Wai, Lo Chor; Jasnie, Farnidah (UiTM Press, 2022)
The Malayan sun bear is the smallest bear species on earth and remains the most diminutive studied bear species. Due to its status as a vulnerable species listed by the IUCN Red list, several conservation efforts have been made, including establishing a conservation centre where confiscated or saved bears were rehabilitated before being released into the wilderness. Thus, it is crucial to know the type of parasite that could negatively impact the bears and thus maintain their welfare in captivity. Parasitic infection is the condition of a parasite infection that has adverse effects on an organism. Intestinal parasitic infection occurs when a parasite infects the gastrointestinal tract of humans or animals. This review paper discusses the recorded parasitic gastrointestinal infections in Malayan sun bears and the methods used to identify those parasites. The review method used was descriptive review. The parasites commonly infecting the Malayan sun bears are Ancylostoma sp. and Trichuris sp. Reports in 1916 and 1929 state that Ancylostoma sp. and Baylisascaris sp. can infect the Malayan sun bear. In 2016, there was a report of Enterocytozoan bienneusi found in Malayan sun bear. Methods used to identify gastrointestinal parasites from faecal samples are the formalin-ether sedimentation technique, centrifugal floatation method, conventional or passive floatation method, and faecal floatation method using the McMaster counting chamber. In summary, information on the parasitic species that infect the gastrointestinal tract of Malayan sun bears is scarce. The most recent study of the gastrointestinal parasite in Malayan sun bear was in 2019, and the identification was only up to the genus level. Detailed identification of gastrointestinal parasites from the Malayan sun bears faecal samples via a molecular technique such as polymerase chain reaction is much needed. Lastly, this review was made to help veterinarians and conservationists maintain Malayan sun bears' welfare in captivity.